The relationship between social support and mental health problems during pregnancy: a systematic review and meta-analysis - Asres Bedaso; Jon Adams; Wenbo Peng; David Sibbritt (BMC, 2021)
Plain language summary Pregnancy is a significant event for reproductive-age women. It is supplemented by hormonal changes and can represent a time of increased risk for the occurrence of mental illness like depression, anxiety and self-harm. Providing good social support for the pregnant mother reduce this risk and prevent pregnancy complication and adverse birth outcome. However, no systematic review and/or meta-analysis has explored the associations between social support and mental illness (depression, anxiety, self-harm) among pregnant women. Therefore, this systematic review and meta-analysis aimed to examine the association between social support and mental illness (anxiety, depression, and self-harm) during pregnancy. The review identified 67 relevant articles with 64,449 pregnant women, from PubMed, Psych Info, MIDIRS, SCOPUS, and CINAHL database. Of the total 67 articles, 22 articles included in the narrative review and 45 articles included in the meta-analysis. Among studies included in the narrative synthesis, a majority of them reported significant positive associations between low social support and antenatal depression, antenatal anxiety and self-harm during pregnancy. Further, the pooled estimates of the meta-analysis show that low social support had a significant positive association with antenatal depression (AOR: 1.18 (95% CI: 1.01, 1.41)) and antenatal anxiety (AOR: 1.97 (95% CI: 1.34, 2.92)). Therefore, maternal health professionals need to have discussions with pregnant women regarding the level and source of social support they receive. Maternal health professionals may also need to consider encouraging the social network of pregnant women to improve social support being given. Policy-makers and those working on maternity care should consider the development of targeted social support programs with a view to helping reduce mental health problems amongst pregnant women.